2017
DOI: 10.3928/01477447-20170810-05
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Morbidity of Lateralization of a Trochanteric Fixation Nail Blade

Abstract: This study examined the incidence and risk factors associated with lateral helical blade migration and trochanteric pain with the trochanteric fixation nail. A retrospective review was performed of 141 cases of pertrochanteric femur fracture treated with a trochanteric fixation nail at a level I trauma center over a period of 42 months. Exclusion criteria included follow-up of less than 60 days, preexisting osteonecrosis of the femoral head, and prophylactic trochanteric fixation nail treatment. Patient demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The helical blade received regulatory approval in 2005 and was designed to provide stronger fixation through impaction of the cancellous bone which should increase resistance to cut-out67). However, several randomized controlled trials comparing helical blade with the lag screw in intramedullary fixations have demonstrated greatly different outcomes compared with published data and theoretical concepts789101112).…”
Section: Introductionmentioning
confidence: 99%
“…The helical blade received regulatory approval in 2005 and was designed to provide stronger fixation through impaction of the cancellous bone which should increase resistance to cut-out67). However, several randomized controlled trials comparing helical blade with the lag screw in intramedullary fixations have demonstrated greatly different outcomes compared with published data and theoretical concepts789101112).…”
Section: Introductionmentioning
confidence: 99%
“…When considering all reasons for revision, previous series have reported revision rates ranging from approximately 2.2%-5%. 4,27,28 In a study by Sandifer et al 10 involving 141 patients, only 2.1% of patients required reoperation due to implant lateralization, yet approximately 20% of patients exhibited lateral hip pain during the final follow-up. Conversely, in another series, only 9% of revisions were related to implant lateralization.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 While a degree of protrusion from the lateral femoral cortex is intrinsic to the surgical technique and is recommended for maintaining biomechanical integrity, in certain instances, the lag screw may be overly protruded during the index procedure due to factors such as limited patient/femur size, miscalculation, or inadvertent oversight. 10 While there is no consensus as to the amount the lag screw should protrude from the lateral trochanteric cortex for a stable construct to be obtained, in some cases, revision surgery, such as change or removal of the lag screw, may be necessary. Considering the fact that most pertrochanteric fractures occur in geriatric patients and that frequent position change while lying in bed is paramount for the avoidance of pressure ulcers, painless laying on the side is further underscored.…”
Section: Introductionmentioning
confidence: 99%